(untitled) (FULafia Journal of Science and Technology, 2018)
The introduction of computer and the advent of internet has changed how man lives in the modern world. The versatility of ICT has led to its adoption in real estate services as property market is imperfect in nature. This makes information about the property not to be well disseminated. This study seeks to investigate the barriers to the deployment of ICT in Nigerian real estate practice. Lagos state was chosen as the case study and delineated based on locational pattern to ascertain the central business districts where the agglomeration of the professional practice of real estate lies. Questionnaires were administered to 172 real estate firms and 516 patrons of the firms within the metropolis. The stratified random and snowballing sampling technique was adopted for questionnaire administration on the population respectively. The data collected was analyzed using the weighted mean score and one sample t-test analysis. Findings revealed that the most salient barrier to the deployment of ICT in real estate practice is the rapid changes in ICT technologies. Recommendations were that practitioners should improve their learning culture on the use all forms of ICT software for real estate practice in the bid to build their level of expertise and also put the profession on a global scale among its contemporaries.